THE EFFECT OF THE WALDORF APPROACH APPLIED WITH THE COOPERATİVE METHOD ON THE EARLY NUMBER ASSESSMENT SKILLS OF 48-60 MONTHS-OLD CHILDREN - Arslan, Aysel; Sebahattin Kartal (International Online Journal of Education and Teaching, 2022)
The aim of this research is to determine the effect of activities in accordance with the Waldorf approach supported by the cooperative method on the early number assessment skills of 48-60 month old children. The study, which was carried out in accordance with the quasi-experimental design design with the control group, was planned as two activity hours two days a week and was applied for four weeks. The study group of the research consisted of 30 children (13 girls-17 boys) in two different kindergartens in the province of Sivas in the spring semester of 2021-2022. In the study, one of the kindergartens was randomly assigned to the experimental group and the other to the control group. Waldorf education materials and cooperative teaching method were used in the experimental group, while the current practice was continued without intervening in the process in the control group. The "Early Number Evaluation Scale for Children" developed by Yılmaz (2015) was used to obtain the data. The reliability of the scale was determined as 0.985 in the scale development study and as 0.939 in this study. Frequency and percentage analysis of participants' demographic information; In the data obtained from the scale, diagnostic statistics, dependent groups t test, independent groups t test were used. According to the findings obtained in the research; It was determined that the scores of the experimental group increased statistically significantly in the pretest-posttest, posttest-permanence test findings of the research groups. Although there was a slight increase in the scores of the control group, it was concluded that this difference was not at a significant level. It was determined that there was a statistically significant difference in favor of the experimental group in the comparison of the scores of the research groups from the post-test and retention test.